THE INFLUENCE OF EXTERNAL FACTORS ON THE FORMATION AND REPRESENTATION NOTATION “ABSANCE” IN LITRACY WORKS BY J. O. BRODSKY - Корнеева, Елена (SWorldJournal, 2020)
The main reasons for the representation of the notion “absence” in the work by J. O. Brodsky and variants its expression at different language levels are considered in the research. The aim of the article is to analyze the connection between the poet’s b